The Importance of Safety Culture for Safe and Quality Care - Lorber, Mateja; Dobnik, Mojca (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Quality in social care institutions is closely linked to resident safety, positive outcomes, and the effectiveness of care. The purpose of the study was to determine the level of safety culture among employees. The results show that employees in social care institutions rate their work competence, meeting patient needs during shifts, and adherence to established standards the highest. The lowest-rated statements relate to staff shortages and challenges in ensuring patient safety. The safety culture is evaluated as good or very good, with no statistically significant differences based on country, gender, or length of service among nursing staff in social care institutions. Communication among employees in social care institutions is also rated as very good, and employee opinions are taken into account. For quality and safe care, teamwork among employees, open communication, and supervisory support are crucial.